Information Research comes to Borås - Karen Nowé Hedvall; Anton Carlander Borgström; Tobias Carlsson; Wout Dillen; Alen Doracic; Elena Maceviciute; Ola Pilerot; Birgitta Wallin; Thomas Wilson (Information Research: An International Electronic Journal)
Introduction. This short paper reflects on the history of Information Research from the perspective of the Swedish School of Library and Information Science at the University of Borås (Sweden), which was entrusted with the journal’s sustainable continuation by its founder Tom Wilson in 2016.